Atrial myxomas causing severe left and right ventricular dysfunction - Aanchal Dixit; Prabhat Tewari; Rashmi Soori; Surendra Kumar Agarwal (Annals of Cardiac Anaesthesia, 2017)
Myxomas are the most common cardiac tumors, accounting for about 50% of benign primary cardiac tumors, with the majority located in the left atrium, and 80% of which originate in the interatrial septum. We report two cases with severe cachexia, neurological sequelae, and severe biventricle dysfunction secondary to atrial myxomas with marked early improvement after tumor excision.